INCREASING STUDENTS’ HIGHER ORDER THINKING SKILL (HOTS) BY USING AUTHENTIC MATERIALS IN TEACHING ENGLISH FOR EFL CLASS - Siti Fachraini; Dewi Sartika (Getsempena English Education Journal, 2019)
Teaching English in educational system nowadays is more focused to increase students’ language skills through transferring knowledge and giving test activities only but less focused on increasing learners’ thinking ability. Higher order thinking skills (HOTS) are one of thinking skills that must be increased in teaching English besides language skills. Furthermore, authentic materials is a good media that can be used in teaching English since they offers the real language and genunine materials to increase learner’s motivation. By using authentic mterials, students can feel the real exposure of the target language they learnt. So that, English learning are more meaningful. This research is experimental study in form of pre-test post-test control group design aimed to investigate the influences of video authentic materials to increase learner’s higher order thinking skills. The participants of this study were English students of STKIP Bina Bangsa Getsempena Banda Aceh. To collect the data, instrument used are tests and questionnaires. Based on data analysis, the result of the study indicated that the scores of students learnt by using video authentic materials increased significantly. It is based on the result of t-test showed that the t- score was 2.641 and the significance score was 0.011. This significance value is smaller than 0.05, so it can be stated that Ha is accepted and Ho is rejected, which means that there is a significant difference in the results of the experimental group post-test and the control group posttest. It can be concluded that teaching Englsih by using authentic video as media can improve English language skills and critical thinking skills of students of STKIP BinaBangsaGetsempena Banda Aceh.